Heparin-Induced Thrombocytopenia in Healthy Individuals with Continuous Heparin Infusion - Williams, Jonathan S.; Autori, Paula J.; Kidd, Stephen K.; Piazza, Gregory; Connors, Molly C.; Czeisler, Charles A.; Scheuermaier, Karine D.; Duffy, Jeanne; Klerman, Elizabeth B.; Scheer, Frank A.; Kozak, Marjorie; Driscoll, Sheila M.; Goldhaber, Samuel Z. (TH Open, 2018)
The risk for developing heparin-induced thrombocytopenia in healthy individuals is thought to be low, but monitoring recommendations remain controversial. Therefore, a retrospective cohort study was conducted to identify the incidence of thrombocytopenic events in a healthy research population exposed and re-exposed to continuous intravenous (IV) unfractionated heparin. The Division of Sleep Medicine and the Centre for Clinical Investigations at Brigham and Women's Hospital, Boston, Massachusetts, United States, instituted a standardized platelet monitoring procedure for all research protocols that involved heparin to detect platelet count decreases. Protocol-related frequent blood sampling required use of continuous IV unfractionated heparin infusion (5,000 unit/L in 0.45% saline at 40 mL/h) to maintain line patency over extended periods of IV access. From the years 2009 to 2012, a total of 273 healthy volunteers enrolled in Sleep Medicine research protocols met study criteria as having been exposed and/or re-exposed to continuously infused intravenous heparin for at least 4 hours. The mean continuous heparin exposure time was 88 ± 82 SD hours with a total of 397 heparin exposure and re-exposure events. Platelet count measurements were obtained on 629 occasions, representing a range from 2 to 9 draws per participant. No platelet count decrease of more than 50% was detected. There were no detected adverse bleeding or thrombotic events. In this retrospective study of healthy volunteers involved in a rigorously applied inpatient platelet monitoring protocol, heparin exposure and re-exposure did not lower platelet concentration and, therefore, does not appear to be associated with increased risk of HIT in this population.
Keywords: healthy volunteer; heparin; platelets; thrombocytopenia